Nutritional Status of Pediatric Intensive Care Patients with Chronic Disease - Özlem Saraç Sandal; Ebru Atike Ongun; Gökhan Ceylan (Galenos Publishing House, 2022)
Objective: This study aims to evaluate the relationship between enteral nutrition and mortality in children with chronic diseases who need to be hospitalized in the pediatric intensive care unit (PICU). Method: The data of the patients who were admitted to intensive care between January 2014 and December 2019 were retrospectively supplied from the hospital database. Demographic data, the presence of underlying diseases, the diagnoses during intensive care admission, the history of previous hospitalization, homecare requirement, the presence of gastrostomy, feeding type during homecare before hospitalization, the amount and type of nutrition were recorded. Results: A total of 186 patients hospitalized in the PICU due to an acute critical illness and with an underlying chronic disease were included in the study. The median age was 49 (17.75-104.5) months, it was observed that 53.8% of the patients were required homecare. The most common chronic disease was central nervous system pathologies accompanied by neurological impairment in swallowing functions (37.3%), while the most common cause of the acute disease was lower respiratory tract infections (48.9%). The overall mortality was 9.7%, and it was found that the majority of the patients who were died were the patients requiring homecare and fed with nasogastric tube at home (p=0.002, p=0.014). Conclusion: It is observed that patients with percutaneous endoscopic gastrostomy are relatively low, hence feeding tube is frequently preferred in children with dysphagia during homecare. However, it is demonstrated that the feeding tube is an independent risk factor for mortality.